The Effects of Kinesio Tape on Isokinetic Muscular Function of Horse Racing Jockeys - Kim, Hyeyoung; Lee, Byounghee (Journal of Physical Therapy Science, 2013)
[Purpose] The purpose of this study was to conduct a scientific analysis of the effectiveness of Kinesio taping at preventing injury and improving horse racing jockey' performance, by studying the effects on isokinetic muscular function of Kinesio taping applied to the knee joint muscle. [Subjects] Eight horse racing jockeys were selected for this study. [Methods] Measurement of isokinetic muscular function of both flexor and extensor muscles was performed at the angular velocities of 60°/sec and 180°/sec using a Biodex system 3, before and after application of Kinesio taping to the rectus femoris, vastus medialis, vastus lateralis, and hamstring. [Result] At the angular velocities of 60°/sec and 180°/sec, significant differences were observed in both flexor and extensor peak torque, average power, and total work of the knee joint after application of Kinesio taping. [Conclusion] The application of Kinesio taping has a positive effect on the function of both knee flexors and extensors, and also kinetic ability. Therefore, its use would lead to a significant increase in the muscle function of horse racing jockeys.